(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2021)
Firstly, the paper presents the Italian constitutional case-law about euthanasia and end-of-life issues, with regards to the significance of the principle of equality among patients in the final phase of their lives. It is argued that the help to suicide by unplugging the machinery without pharmacological or mechanical supports by the care givers must be considered as a violation of the principle of reasonableness. Secondly, the contribution addresses the existence of a fundamental right not to live in conditions of grave suffering. Otherwise, the law would violate the principle of equality and the right to self-determination would be unduly compressed.